About the Commonality of Poetic Forms - Aldasheva Shirin Jalgasovna (Peerian Journals Publishing, 2022)
In the article, the poetic form of the quatrain and the ruby genre are analyzed based on the scientific views of scientists in the literature of Uzbek and world nations.
Keywords: quatrain; category; rubai; poetry